O conceito de leitura da Prova Brasil - Fuza, Ângela Francine (2010)
Current research is linked to the Research Group "Interaction and Writing" (UEM/CNPq- www.escrita.uem.br) and to research project "Evaluation practices in reading and reader's formation", developed at the State University of Maringá PR Brazil. It is underpinned by theories in reading derived from the theoretical principles of Enunciation Linguistics, Applied Linguistics and the social and historical perspective of teaching-learning through the interaction notion of language. Research aims at understanding the manner the concept of reading and its characteristics buttress the nationwide schooling evaluation called "Prova Brasil". A survey of aspects linked to reading and presented by the Reference Matrix was undertaken. Focus on reading as interaction and perceived as a process has been verified. After analyzing each and every Topic it has been verified that all evaluate reading. However, according to the keywords, the first Topic, Reading Procedures, focuses on reading as a process, whereas other concentrate on genre, intertextuality, coherence and cohesion in text processing and the use of expressive resources and meaning effects. Topic One of the National Evaluation System of Fundamental Education's Reference Matrix, called Reading Procedures, was chosen for analysis, with special reference to one of the keywords and a representative sample of what would be reading activities. Analysis of keywords and reading features revealed reading as interaction in official documents that underpin the construction of the "Prova Brasil" and reading's evaluation features. From the most superficial levels to its most complex ones, reading as a process was thus highlighted.